Smart Low Head Picohydro System with QHBM Optimization for Rural Electrification and Innovation - ARIPRIHARTA ARIPRIHARTA; MOKH. SHLIHUL HADI; NANDANG MUFTI; SATIA NUR MAHARANI; MUHAMMAD CAHYO BAGASKORO; SASMITA BAGUS SANG KESUMA ANANTA; PRIA EKA RESWANA (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2025)
This study develops a low-head smart picohydro system for rural electrification optimized using the Queen Honey Bee Migration (QHBM) algorithm. The system includes a propeller turbine, axial generator, charge controller, inverter, and battery. QHBM optimizes flow rate, head, system efficiency, output power, and energy cost to achieve the best technical and economic performance. For comparison, Particle Swarm Optimization (PSO) is used, known for its fast convergence but prone to local optima. Results show that at a 0.65 m head, QHBM produces 546.68 W, higher than PSO (546.48 W) and manual calculation (530 W), with 50% faster convergence. The proposed system supports sustainable and affordable energy access for off-grid communities and offers potential for renewable energy startup innovation.